Grundlagen der anaeroben Leistungsdiagnostik - Heck, H.; Mader, A.; Schulz, H. (Deutsche Zeitschrift für Sportmedizin, 1998)
Testing procedures for the assessment of anaerobic energy metabolism during muscular work have not yet gained the relevance of tests assessing maximal aerobic power. The diagnosis of aerobic power allows - through the choice of an adequate test protocol - to de-sign a test which mainly measures the power of the aerobic metabolism by means of indi-cators like Ozmax and lactate. With regard to tests for the assessment of anaerobic power and capacity, however, alactic, lactic and oxidative components of energy expenditure as a whole cannot be distingished by means of simple parameters (for example lactate and time until exhaustion). By means of Computer simulations of energy metabolism for supramaximal loads with durations until exhaustion of about 10 s and 60 s as well as the isola-ted Variation of the concentration of muscle phosphocreatine, the maximal rate of lactate production and the maximal aerobic power `VChmax) the influence of the single compo-tents on energy metabolism as a whole is pre-sented in a semi-quantitative way. A testing battery for a detailed assessment of all single components should include a maximal test with a duration of 5 s (power and capacity of the alactic system), a maximal test with a duration of 10 s (assessment of the power of the glycolytic system), an all-out test (40 to 100 s) with lactate measurement (assessment of lactic capacity) and the measurement of Ozmax.